PERAN PERSERIKATAN BANGSA-BANGSA DALAM PENYELESAIAN SENGKETA INTERNATIONAL - Ahmad Basuki (Perspektif, 2003)
In developing interstate relationships, there frequently are different interests that develop into an international dispute. For the purpose anticipating the international dispute development turn into international instability then the International Law should facilitate for problem solving procedures such as involving United Nation. The role of the United Nation in solving international disputes can be done by applying the procedures of Security Board General Committee and Secretary General based on the their own proportion and authority.